Zirconium dioxide implants as an alternative to titanium: A systematic review - Comisso, Ivana (J Clin Exp Dent, 2021)
BACKGROUND: This systematic review evaluates the available scientific literature to demonstrate the aesthetic and clinical benefits and to determine the survival and the success of zirconium dioxide implants concerning titanium implants. MATERIAL AND METHODS: The electronic databases were searched until January 2020. Outcome measures were pink aesthetic score (PAS), white aesthetic score (WAS), bleeding on probing (BOP) and probing depth (PD). The addressed PICO question was: In partially edentulous patients in the upper-anterior sector, do zirconium dioxide implants provide aesthetic benefits over conventional titanium implants? RESULTS: In the 15 articles included after the screening were evaluated respectively, the pink aesthetic score, white aesthetics score, the peri-implant, and crown index, bleeding on probing, plaque index, probing pocket depth, radiographic bone loss, papilla height, and survival and success rate. The results show how the aesthetic and clinical benefits and the survival and success rate of zirconium dioxide implants are, in general, better than titanium implants. CONCLUSIONS: Despite the optimal aesthetics, clinical and survival results obtained in the review, more studies are needed to confirm these data. Key words:Ceramic dental implants, zirconia implants, esthetics, zirconium dioxide and zirconia.